COMPLIANCE INDEX ANALYSIS AND TOTAL FACTOR PRODUCTIVITY OF SEED YAM PRODUCTION TECHNOLOGIES IN NORTH-CENTRAL NIGERIA - Morolake Bolaji; Raphael Olarewaju Babatunde; Olubunmi Abayomi Omotesho; Sunday Onwuaroh (Socio-Economics/Agribusiness Department, 2023)
Technology adoption for increased productivity can only be relevant when technologies introduced are adequately complied with. This study assessed the level of compliance by CAY -Seed and NRCRI-Seed yam farmers to the usage of the seed yam production technologies and examined the productivity of the CAY- Seed and NRCRI - Seed yam farmers’ farms. The study adopted a multi-stage sampling technique and a total of 283 respondents were used for the study. In addition, the study made use of cross-sectional data which were analysed using descriptive statistics, compliance index and total factor productivity. The findings of the study revealed that CAY-Seed yam farmers optimally complied (0.8932) with the usage of the seed yam technologies than their NRCRI counterparts (0.5982). Similarly, NRCRI-Seed yam farmers’ farms had a higher TFP (1.9133) compared to CAY-Seed yam farmers’ farms (1.8009). Seed yam farmers should take up and super-optimally utilize all improved agricultural (bio-farming activities) technologies made available to them. Similarly, trainings and intervention projects meant to improve productivity of seed yam farms should be established in areas where productivity of agricultural produce is low.